(untitled) (Innovation & Development in Engineering and Applied Science, 2026)
The material factor is one of the most important aspects to take into account when designing and planning a suitable industrial plant layout. With a correct distribution it is possible to improve the efficiency, productivity, safety in the production plant, the quality of the products, the flexibility and the adaptability of the company. To achieve an appropriate plant layout, it is necessary to consider the material factor, its nature, its weight and volume, production processes, storage and handling requirements, and safety and quality requirements.